Key Hub and Bottleneck Genes Differentiate the Macrophage Response to Virulent and Attenuated Mycobacterium bovis - Killick, Kate E.; Magee, David A.; Park, Stephen D. E.; Taraktsoglou, Maria; Browne, John A.; Conlon, Kevin M.; Nalpas, Nicolas C.; Gormley, Eamonn; Gordon, Stephen V.; MacHugh, David E.; Hokamp, Karsten (Frontiers in Immunology, 2014)
Mycobacterium bovis is an intracellular pathogen that causes tuberculosis in cattle. Following infection, the pathogen resides and persists inside host macrophages by subverting host immune responses via a diverse range of mechanisms. Here, a high-density bovine microarray platform was used to examine the bovine monocyte-derived macrophage transcriptome response to M. bovis infection relative to infection with the attenuated vaccine strain, M. bovis Bacille Calmette–Guérin. Differentially expressed genes were identified (adjusted P-value  0.01) and interaction networks generated across an infection time course of 2, 6 and 24 h. The largest number of biological interactions was observed in the 24 h network, which exhibited scale-free network properties. The 24 h network featured a small number of key hub and bottleneck gene nodes, including IKBKE, MYC, NFKB1 and EGR1 that differentiated the macrophage response to virulent and attenuated M. bovis strains, possibly via the modulation of host cell death mechanisms. These hub and bottleneck genes represent possible targets for immunomodulation of host macrophages by virulent mycobacterial species that enable their survival within a hostile environment.